Application of universal neutral reactor in shunt compensated transmission lines: feasibility study. Issue 9 (6th April 2018) - Jafarian, Peyman; Eskandari, Hamid; Sanaye‐Pasand, Majid
Abstract : Single‐phase neutral reactors are used in shunt compensated transmission lines (TLs) to accelerate the extinction of the secondary arc through suppression of the arc current. Application of similar shunt reactors with the same capacities is prevalent in the transmission systems. Using the traditional method, however, for each TL, a specially designed neutral reactor is needed that could be in some cases extremely large and practically infeasible. This study investigates the feasibility of application of a properly designed neutral reactor, which is independent of the line length. This solution only depends on the ratio of positive‐ and zero‐sequence capacitances of the line as well as the shunt reactor inductance. Accordingly, for all TLs at the same voltage level equipped with shunt reactors of the same capacities, the proposed neutral reactance would be almost identical which helps to minimise the cost and design complexity. Meanwhile, the required insulation level would be kept sufficiently small for any compensation degree. Based on the steady‐state analysis and time‐domain simulations conducted using the electromagnetic transient program, it is shown that for the majority of TLs, it is possible to extinguish the secondary arc within an acceptable short period of time by applying the proposed neutral reactor.